CURRENT & COMPARATIVE STUDY ON THE PRODUCTIVITY AND QUALITY OF TASAR SILKWORM, ANTHERAEA MYLITTA D. (SATURNIIDAE: LEPIDOPTERA) (International Journal of Food and Nutritional Sciences, 2023)
Silk is the most beautiful, wonderful and precious gift given by the nature. Silk and silk product areused for different purpose whether medicine, cosmetics and cloths etc and having many other uses.Silk is the most common rearing agro based industries world wise practicing and is not onlyvaluable this is ultimate and wonderful boon of the nature are produced by Sericigenousinsects belonging families Bombycidae and Saturniidae of order Lepidoptera.